Criminal Procedure Policy Related to the Provision of Legal Aid in Criminal Cases (Study in DPC PERADI Sibolga City) - Harahap, Ahmad Raihan; Yunara, Edi; Putra, Mohammad Eka (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
This article examines the provision of legal aid to the underprivileged in criminal cases as categorized in Article 56 of the Criminal Procedure Code regarding the suspect's right to legal aid. This type of research uses normative legal research supported by empirical data, through the Statute Approach. This article explains how the provision of legal aid in criminal cases, which until now its implementation is still not in accordance with the current regulations, as well as what obstacles and efforts can be made to create equality before the law, and also the regulation in Article 146 paragraph (4) of the Draft Criminal Procedure Code (RKUHAP) which has decreased from the previous regulation in Article 56 of the Criminal Procedure Code, the results obtained from this study are that there are still many law enforcement officers in Sibolga City when carrying out their duties in terms of providing legal aid that is not in accordance with the provisions of the law, this article aims to find out, analyze the regulations, processes, obstacles and collective efforts to improve the regulation of legal aid, especially in criminal cases and realize equal distribution of legal aid.